(untitled) (Research, Society and Development, 2019)
The history of early childhood education is relatively recent in Brazil, dating from the late nineteenth century and assuming a welfare character. Following this trend, the origin of the Municipal Center for Early Childhood Education (CMEI), Professor Libânia Medeiros in the city of Natal / RN, is related to the movement of expansion of kindergartens between the 1970s and 1980s. The objective of this study is to reconstruct the history of the Municipal Center of Early Childhood Education Professor Libânia Medeiros through documentary and bibliographical sources. With regard to the methodology used, it can be said that this is a qualitative research, that adopted as methodological procedures the analysis of documentary and bibliographic source. Among the theoretical and documentary referential used are, Abramovich and Majskop (1995); Arroyo (1994) Barbosa and Horn (2001), Craidy and Kaercher (2001); Law No. 9.394/96; Resolution 002 of May 20, 2008; Decree No. 9.375/11 and the pedagogical political project of the CMEI (2017), among others. Finally, the study showed that the legal creation of the CMEI was a process that happened in a gradual way, perceiving changes as to the functionality as well as the purpose of the education offered. The CMEI, professor Libânia Medeiros, experienced significant changes, which led her from daycare to CMEI, becoming an institution concerned with the integral development of the child and the indissociability of caring, educating and playing, and not understanding early childhood education as a welfare worker.